Technology of natural juice production and its human health influence - Yakubovskaia, V. V. (ТДАТУ, 2019)
Juices obtained from ripe fresh products provide cells and tissues with all the necessary elements and enzymes that are easily digestible for the body.
Keywords: nutrition; healthy diet; fruits and vegetables